Russian Pronouns and Their Types (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides an overview of pronouns in the Russian language, explaining their classification and functions. It discusses the main types of pronouns, such as personal, demonstrative, possessive, reflexive, interrogative, relative, and indefinite pronouns. The article is designed to aid learners in understanding the role and usage of pronouns in Russian grammar.